Development of a highly sensitive real-time one step RT-PCR combined complementary locked primer technology and conjugated minor groove binder probe - Hong, JiYoung (BioMed Central, 2011)
BACKGROUND: Enterovirus (EV) infections are commonly associated with encephalitis and meningitis. Detection of enteroviral RNA in clinical specimens has been demonstrated to improve the management of patients, by ruling out other causes of disease. METHOD: To develop a sensitive and reliable assay for routine laboratory diagnosis, we developed a real-time one step reverse transcription polymerase chain reaction (RT-PCR) assay with minor groove binder probes and primers modified with complementary locked primer technology (TMC-PCR). We checked the sensitivity of the developed assay by comparing it to a previously published TaqMan probe real-time one-step RT-PCR (TTN-PCR) procedure using enteroviral isolates, Enterovirus Proficiency panels from Quality Control on Molecular Diagnostics (QCMD-2007), and clinical specimens from patients with suspected EV infections. RESULTS: One hundred clinical specimens from 158 suspected viral meningitis cases were determined to be positive by the TMC-PCR assay (63.29%), whereas only 60 were found to be positive by the TTN-PCR assay (37.97%). The positive and negative agreements between the TMC-PCR and TTN-PCR assays were 100% and 59.2%, respectively. CONCLUSION: This data suggest that the TMC-PCR assay may be suitable for routine diagnostic screening from patient suspected EV infection.